2019
DOI: 10.3390/nu11040934
|View full text |Cite
|
Sign up to set email alerts
|

Antiperiodontitis Effects of Magnolia biondii Extract on Ligature-Induced Periodontitis in Rats

Abstract: Over the past decades, periodontitis has become a rising health problem and caused various diseases. In the many studies shows that some extracts and compound to the prevention and treatment of periodontitis. This study focuses on the effects of inhibition of gingival damage and alveolar bone loss. The aim of this study was to evaluate the protective effects of Magnolia biondii extract (MBE) against ligature-induced periodontitis in rats. A ligature was placed around the molar teeth for 8 weeks, and MBE was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…Induction of periodontitis in the current study was performed by using 4-0 silk ligature for 2 weeks. This is in accordance to Moraes et al (2020) (25) and other researchers (26,27) who used silk ligatures to induce experimental periodontitis because it is a simple, effective, cheap and an available method. In addition, Kurt et al (14) proved that tying silk ligatures around the experimental rats' mandibular first molars for 2 weeks was capable to create an experimental periodontitis model.…”
Section: Discussionsupporting
confidence: 91%
“…Induction of periodontitis in the current study was performed by using 4-0 silk ligature for 2 weeks. This is in accordance to Moraes et al (2020) (25) and other researchers (26,27) who used silk ligatures to induce experimental periodontitis because it is a simple, effective, cheap and an available method. In addition, Kurt et al (14) proved that tying silk ligatures around the experimental rats' mandibular first molars for 2 weeks was capable to create an experimental periodontitis model.…”
Section: Discussionsupporting
confidence: 91%
“…Необхідно зазначити, що для проведення діагностики та розробки оптимальної схеми терапії при даній патології необхідні ґрунтовні дослідження структурної організації складових компонентів пародонта на різних термінах дії опіоїдів та подальшої відміни цих чинників [9]. При цьому, як відзначають дослідники, експериментальне моделювання патологічних станів на тваринах і досі залишається актуальним [10,11]. Усе вищезазначене зумовило напрямок експериментального дослідження.…”
Section: Results At the End Of Week 10 Of The Experiment No Clear Dyn...unclassified
“…Pro-inflammatory cytokines, Tnfa and Il1b , have been shown to initiate bone resorption in periodontal diseases [ 51 , 52 ]. Tnfa levels in rats with periodontitis are significantly higher than those of normal rats after 6 weeks of ligature induction [ 53 , 54 ]. The present study revealed that bubaline fibrin glue treatment led to decreased mRNA expression of Tnfa and Il1b in a time-dependent manner, and a significant difference was noted compared to the non-treatment control.…”
Section: Discussionmentioning
confidence: 99%